Pengaruh Kompetensi dan Kompensasi Terhadap Komitmen Organisasional Serta Implikasinya pada Kepuasan Kerja : Studi Kasus pada Karyawan di Hotel Ogh Doni Jogjakarta - Maria Yunita Meme Siba; Zulkifli Zulkifli; Soedjono Soedjono (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
The aim of this research is to analyze the influence of competence and compensation on organizational commitment and its implications for job satisfaction. It is hoped that this research will provide theoretical benefits for writers and readers as well as practical benefits for companies or organizations in managing human resources. This research is quantitative research, which was carried out at the Ogh Doni Hotel Jogjakarta by using 30 employees as the population and the research sample was determined using a purposive sampling technique. The results of this research show that in the first regression model the competency and compensation variables partially and simultaneously have a positive and significant effect on organizational commitment. Meanwhile, in the second model, it is known that competence, compensation and organizational commitment have a partial and simultaneous effect on employee job satisfaction.